Pleiotropic alterations in gene expression in Latin American Fasciola hepatica isolates with different susceptibility to drugs. - Radio, S. (2019)
Background Fasciola hepatica is the main agent of fasciolosis, a zoonotic disease affecting livestock worldwide, and an emerging food-borne disease in humans. Even when effective treatments are available, drugs are costly and can result in tolerance, liver damage and normally they do not prevent reinfection. Drug-resistant strains in livestock have been reported in various countries and, more worryingly, drug resistance in human cases has emerged in South America. The present study aims to characterize the transcriptome of two South American resistant isolates, the Cajamarca isolate from Peru, resistant to both triclabendazole and albendazole (TCBZR/ABZR) and the Rubino isolate from Uruguay, resistant to ABZ (TCBZS/ABZR), and compare them to a sensitive strain (Cenapa, Mexico, TCBZS/ABZS) to reveal putative molecular mechanisms leading to drug resistance. Results We observed a major reduction in transcription in the Cajamarca TCBZR/ABZR isolate in comparison to the other isolates. While most of the differentially expressed genes are still unannotated, several trends could be detected. Specific reduction in the expression levels of cytoskeleton proteins was consistent with a role of tubulins as putative targets of triclabendazole (TCBZ). A marked reduction of adenylate cyclase might be underlying pleiotropic effects on diverse metabolic pathways of the parasite. Upregulation of GST mu isoforms suggests this detoxifying mechanism as one of the strategies associated with resistance. Conclusions Our results stress the value of transcriptomic approaches as a means of providing novel insights to advance the understanding of drug mode of action and drug resistance. The results provide evidence for pleiotropic variations in drug-resistant isolates consistent with early observations of TCBZ and ABZ effects and recent proteomic findings.